Analysis of the Occupational Health and Safety Management System (SMK3) in the Santika Premiere Padang Hotel Development Project - Rafki Imani; Kharisma Permata Sari; Yogi Andzel Pratama (Universitas Putra Indonesia YPTK Padang, 2021)
Occupational safety and health are the main means of preventing accidents, disability and death as a result of work accidents. K3 aims to prevent, reduce, and even eliminate the risk of work accidents (zero accident). The application of this concept should not be considered as an effort to prevent work accidents and occupational diseases that cost the company a lot of money, but should be considered as a form of long-term investment that will provide abundant benefits in the future. This study aims to determine the implementation of the implementation and the level of success, as well as to determine the factors causing the delay in the implementation of the occupational safety and health management system (SMK3) in the construction project of the Hotel Santika Premiere Padang.The stage of this research is the study of various existing literatures to determine the variables to be used. The next stage is designing research questionnaires and then collecting data by distributing questionnaires directly to the field. The data obtained from the questionnaire will be analyzed for validity and reliability tests using the Statistical Package for Social Science (SPSS) software.The results of this study indicate that the success of the implementation of the occupational safety and health management system (SMK3), which is taken from the average sum of all variables, is 98.5%. So that it can be concluded that the level of achievement of the successful implementation of SMK3 in the construction project of the Hotel Santika Premiere Padang is based on the determination of the success value written in the Minister of Permenaker Number: 05/MEN/1996, eligible for a certificate and a gold flag. This is in accordance with category number 3, namely